Just-in-time - Sandras, Jr. William A. (Oliver Wight Limited Publications, 1989)
Based on his extensive experience Sandras reveals a complete procedure for successfully managing all of the challenges and possible obstacles in an actual implementation. Organizing the implementation team, developing a working Kanban system, restructuring the shop floor, creating efficient connections between suppliers and customers, measuring performance and integrating JIT with TQM are among the issues discussed. --This text refers to the Hardcover edition.